Rent control and rental prices: High expectations, high effectiveness? - Philipp Breidenbach; Lea Eilers; Jan Fries (RWI - Leibniz-Institut für Wirtschaftsforschung, 2019)
This paper evaluates the rent control policy implemented in Germany in 2015. Like many countries around the world, German cities and metropolitan areas have experienced a strong increase in rental prices during the last decade. In response, the politicians aimed to dampen the rise in rental prices by limiting the landlords' freedom to increase rents for new contracts. To that end, the rent control was introduced. To evaluate the effectiveness of the rent control with respect to rental prices, we take advantage of its restricted scope of application. First, it is applied only in a selected number of municipalities, thereby generating regional variation. Second, the condition of rental objects generates an additional dimension of variation since new and modernised objects are exempt from rent control. Based on data for rental offers in Germany, we apply a triple-difference framework with regionspecific time trends as well as flat type-specific ones. Despite the high political expectations, our estimates indicate that the German rent control dampens rental price by only 2.5%. This effect varies across object characteristics and seems to be larger for lower-quality dwellings and in the lower price segment. Nevertheless, the application of an event-study indicates that these effects are not persistent over time. – – Im Juni 2015 ist das Mietnovellierungsgesetz in Kraft getreten. Dieses Gesetz räumt den Bundesländern ein, Gemeinden mit angespanntem Wohnungsmarkt zu definieren und mithilfe der Mietpreisbremse Preisanstiege bei Neuvermietungen zu regeln. Um negative Anreize für die Modernisierung oder den Neubau von Objekten zu vermindern, hat der Gesetzgeber diese Objekte von der Mietpreisbremse ausgenommen. Um die Effektivität der Mietpreisbremse auf die Mietpreise zu evaluieren nutzt diese Studie diese Ausnahmen und die unterschiedliche Einführung auf lokaler und zeitlicher Ebene aus. Grundlage der empirischen Untersuchung bilden georeferenzierte Mietangebote (RWI-GEO-RED) und die Anwendung eines Diff-in-Diff-in-Diff Modells. Somit kann insbesondere für die Endogenität der kommunalen Einführung einer Mietpreisbremse kontrolliert werden, weshalb Probleme der kausalen Analyse überwunden werden können. Die Ergebnisse zeigen robuste, aber schwache preisdämpfende Effekte der Mietpreisbremse, die für Wohnungen im unteren Preissegment, mit niedriger Ausstattung am höchsten sind. Im Rahmen einer Event-Study werden die Ergebnisse verifiziert und hinsichtlich der Wirkungsdauer betrachtet. Dabei zeigt sich, dass diese Preiseffekte nach einem Jahr nicht mehr beobachtbar sind.
Keywords: C23; R31; 330; rental prices; rent control; regional variation; regulation; diff-in-diff-in-diff; event study